Analisis Aspek Usability Pada Aplikasi DANA Di Kalangan Masyarakat Kota Jambi Menggunakan SUS - Ingriana, Alberta; Mulyono, Herry (LPPM STIKOM Dinamika Bangsa, 2025)
The Fund application is an application that was founded in 2017 by Vincent, a young Indonesian where the Fund application is a startup that provides an e-money platform for Indonesians to be able to make non-cash and non-card transactions. This study aims to apply usability values ​​to the DANA application by using the System Usability Scale (SUS) and to analyze and evaluate the application of the System Usability Scale (SUS) to the DANA application. Based on the System Usability Scale (SUS) method to measure how well the quality of this application is used, data was collected by distributing an indirect questionnaire containing 10 questions to 272 respondents who are Jambi city residents who have used the DANA application. The results of this study through validity and reliability tests, all data in this study were declared valid and reliable.